Diversity Of Approaches In Teaching Different Age Groups: Diversity Of Approaches In Teaching Different Age Groups - Rashidov, Sanjar (Журнал иностранных языков и лингвистики, 2022)
The paper considers the diversity of approaches in teaching different age groups. Besides, the classic and contemporary definitions of approaches in teaching different age groups are partially presented in contrastive mode. The precise categorical reference of teaching phenomenon has been also touched upon. The initial researches and various attitudes on approaches in teaching have been discussed and analyzed in the paper.